Decentralization and Progressive Taxation - Simon Berset; Mark Schelker (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The traditional normative literature on fiscal federalism argues that redistributive policies should be centralized in order to avoid welfare- or tax-induced migration. However, recent evidence shows that even in a setup where the progressivity of the income tax schedule is centralized to an upper-layer government and local governments are involved in tax competition with only a tax shifter, local mobility induces income sorting. Hence, despite centralized redistributive taxation, the resulting effective tax schedule is less progressive than what is set in the tax code. We argue that upper-layer governments anticipate the impact of local income sorting and strategically adjust their statutory tax schedules. We analyze Swiss panel data and apply causal machine learning methods to identify the effects of decentralization on the statutory tax structure. We provide evidence that more decentralized cantons reduce the tax burden for lower and intermediate income classes and hence implement more redistributive statutory tax schedules. This strategic adjustment is limited by the mobility of the tax base.
Keywords: H73; H77; H71; 330; fiscal federalism; decentralized taxation; redistribution; progressive income taxes